Enantio‐separation of pregabalin by ternary complexation using trapped ion mobility spectrometry. (16th February 2021) - Gu, Liancheng; Yang, Shutong; Wu, Fangling; Xu, Fuxing; Yu, Shaoning; Zhou, Mingfei; Chu, Yanqiu; Ding, Chuan‐Fan
Abstract : Rationale The rapid identification of small‐molecule chiral drugs is challenging due to subtle structural differences. Different enantiomers of chiral drugs may produce inverse biological effects through their different pharmacokinetics. Therefore, it is highly desirable to distinguish the chirality of drug molecules. Methods: The chirality of pregabalin was distinguished by studying the ion mobility spectra of the ternary non‐covalent complexes formed with cyclodextrins (CDs), pregabalin, and alkali‐earth cations using trapped ion mobility spectrometry (TIMS). The ternary non‐covalent complex ions were determined by electrospray ionization of mixed solutions. The analyzed sample was simply mixed, without derivatization or sample pretreatment. The relative contents of pregabalin enantiomers were derived using a calibration curve method. Results: The ion mobility spectra of several ternary non‐covalent complexes formed with α‐, β‐, and γ‐CD, pregabalin, and alkali‐earth cations were obtained. We compared their ability to distinguish the chirality of pregabalin. The best peak‐to‐peak resolution ( R p‐p ) was estimated to be 2.20 for [2β‐CD + pregabalin + Sr] 2+, which can be ascribed as baseline separation. The derived relative contents for S‐pregabalin were in agreement with the actual contents. Conclusions: A novel and convenient method for discriminating the chirality of the pregabalin molecule by TIMS was developed and optimized. The chirality of pregabalin was recognized by studying the ion mobility spectra of the ternary non‐covalent complexes, such as [2β‐CD + pregabalin + Sr] 2+ . This TIMS method could also be used to quantify the relative contents of pregabalin enantiomers.